CLINICAL EVALUATION OF PANCHKOLAPHANT IN THE MANAGEMENT OF MANDAGNIJANYA STHAULYA WITH SPECIAL REFERENCE TO OBESITY - Twinkle, Gupta; Jagmeet, Kaur; Shamma, Sharma; bala, Neerajbala; Ekta, Kapoor (International Journal of Ayurveda and Pharma Research, 2015)
Obesity is one among the major diseases of modern era, increasing in prevalence. The Word Health report of W.H.O. listed Obesity under 10 top selected risks to the health. Sthaulya (Obesity) is well known from the Samhita period and is considered to be one of the eight undesirable conditions (Ashta Nindita). It can be caused due to Mandagni as Agni is considered to be responsible for metabolism. Thus, Ama formed moves within body, further causing Medovruddhi, which produces excessive stoutness. According to modern science, one of the causes for obesity is sedentary lifestyle, where there is more intake of junk food and less physical activity. This also signifies in increased BMI, further leading to obesity. In order to treat this problem, 30 patients of Sthaulya were registered to evaluate Sthaulya management with Panchakola Phant. Panchakola Phant containing Shunthi, Pippali, Pippalimula, Chavya, Chitrak; being Katu Rasaatmak helps in digestion and removal of Ama from body and further helps in management of Meda Dhatu Dushti. Patients were assessed on the basis of signs and symptoms before starting the treatment and administered Panchakola Phant. Duration for treatment was 3 months and patients were regularly followed up after 1 month to evaluate the clinical effects of the trial drug.